Significance of the angiotensin I/angiotensin II/angiotensin‐(1‐7) axis in the pathogenesis of systemic sclerosis - Miziołek, B.; Bergler‐Czop, B.; Kucharz, E.; Kotyla, P.; Kopeć‐Mędrek, M.; Widuchowska, M.; Sieńczyk, M.; Brzezińska‐Wcisło, L. (Journal of the European Academy of Dermatology and Venereology, 2020)
Background Systemic sclerosis (SSc) is a multisystemic disease with an extensive microvasculopathy. Previously, disturbances in plasma levels of angiotensin II (Ang II) and its antagonistic angiotensin‐(1‐7) (Ang‐(1‐7)) were found in patients with SSc. Their significance in a pathogenesis of SSc stays unclear due to discrepancies of earlier studies. Objectives To evaluate a significance of disturbances in production pathway of angiotensins in a development of SSc. Methods There were enrolled 27 patients with established SSc, 23 subjects with very early SSc and 23 healthy controls. The diagnosis of SSc was established in patients who met EULAR/ACR 2013 classification criteria. Very early SSc described patients with Raynaud's phenomenon having SSc‐specific antinuclear antibodies and SSc‐like abnormalities in nailfold videocapillaroscopy. Patients were submitted to evaluation of internal organ involvement and blood sampling to assay plasma levels of angiotensin I, angiotensin II and angiotensin‐(1‐7) with ELISA technique. Results Plasma level of angiotensin‐(1‐7) was significantly reduced in both SSc group (median = 47.2 pg/mL; P < 0.001) and ones with very early SSc (median = 102.7 pg/mL; P = 0.002) when compared to healthy controls (median = 176.1 pg/mL). A tendency to higher than in control group (median = 214 pg/mL) plasma level of angiotensin I was seen in SSc group (median = 392 pg/mL; P = 0.059). Differences in plasma level of angiotensin II were insignificant between all study groups. Those disturbances produced unfavourable angiotensin‐(1‐7)/angiotensin II (%) ratio in both groups of patients, which achieved statistical significance in subjects with established SSc (P < 0.001). Production pathway of angiotensins showed a dependence on a subtype of SSc, immune profile and a presence of interstitial lung disease. Conclusions Production of angiotensin‐(1‐7) was significantly reduced in both SSc patients and those ones with very early SSc, although a significant imbalance between angiotensin II and angiotensin‐(1‐7) occurred only in subjects with established disease.